The Effect of Aloe Vera Peel Extract on Histopathology of Rat Pancreas Induced by Alloxan - R Susanti; Eka Setiadi; Endah Peniati (Biosaintifika: Journal of Biology & Biology Education, 2019)
The Extract of Aloe Vera Peel (EAVP) contains bioactive compounds (flavonoids, alkaloids, tannins, saponins, and phenolics) that it thought to improve pancreas histopatology on rat with diabetes mellitus, therefore it has potential for diabetes mellitus treatment. This research aimed to figure out the effect of EAVP on improving the histopathology of rat pancreas induced by alloxan. This research was an experimental study using a completely randomized design with a randomized post-test design. A total of 25 rats were divided into 5 groups: C(-) was a normal group, fed and drinking standard; C(+) was positive control group, induced by alloxan 120 mg/kgBW; PI, PII and PIII were groups that were induced by alloxan 120 mg/kgBW and were given a full-dose of EAVP of 87.5, 175 and 350 mg/kgBW respectively. The data was assessed using the Kruskal-Wallis and Mann-Whitney statistical analysis. The results of the statistical test showed that the histopathology of rat pancreas of the C(+) group were significantly different compared with the treatment group. Meanwhile, the representation of histopathology of pancreas between PIII and C(-) were not significantly different. It can be concluded that treating hyperglycemia rats with the EAVP for 28 days can improve the representation of histopathology of rat pancreas. At the laboratory level, EAVP has been shown to repair rat pancreatic damage. With this result, Aloe vera has the potential to be developed as a phytopharmaca for the prevention or treatment of diabetes mellitus.